EVOLUTIONARY APPROACH IN MEDICAL EDUCATION: HOW UNDERSTANDING BIOLOGICAL PATTERNS HELPS A PHYSICIAN (Uzbekistan Open Conference, 2025)
The article examines the role of the evolutionary approach in modern medical education. It is shown that the integration of knowledge from evolutionary biology contributes to the formation of systemic thinking among students, helps to better understand the mechanisms of adaptation and pathogenesis, and develops the scientific worldview of a physician. The paper analyzes the current state of teaching natural sciences in medical universities of Russia and Uzbekistan, identifies existing problems, and outlines prospects for their solution. Special attention is paid to methodological techniques for implementing the evolutionary approach in the educational process.